Zebrafish circadian clocks: cells that see light. (26th October 2005) - Tamai, T.K.; Carr, A.J.; Whitmore, D.
Abstract : In the classical view of circadian clock organization, the daily rhythms of most organisms were thought to be regulated by a central, 'master' pacemaker, usually located within neural structures of the animal. However, with the results of experiments performed in zebrafish, mammalian cell lines and, more recently, mammalian tissues, this view has changed to one where clock organization is now seen as being highly decentralized. It is clear that clocks exist in the peripheral tissues of animals as diverse as Drosophila, zebrafish and mammals. In the case of Drosophila and zebrafish, these tissues are also directly light-responsive. This light sensitivity and direct clock entrainability is also true for zebrafish cell lines and early-stage embryos. Using luminescent reporter cell lines containing clock gene promoters driving the expression of luciferase and single-cell imaging techniques, we have been able to show how each cell responds rapidly to a single light pulse by being shifted to a common phase, equivalent to the early day. This direct light sensitivity might be related to the requirement for light in these cells to activate the transcription of genes involved in DNA repair. It is also clear that the circadian clock in zebrafish regulates the timing of the cell cycle, demonstrating the wide impact that this light sensitivity and daily rhythmicity has on the biology of zebrafish.